Human Resource Management Strategy for Optimizing Elementary School Teacher Professionalism - Darmawan, Andi; Hasanah, Enung; Zuhaery, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the Human Resources (HR) management strategy in optimizing teacher professionalism at Muhammadiyah Condongcatur Elementary School. Teacher professionalism is a key pillar in ensuring the quality of education at the elementary school level, but the challenges of curriculum dynamics and workload require a comprehensive managerial strategy. This study uses a qualitative approach with a case study. Data were collected through in-depth interviews with the Principal, Vice Principal, and Teachers, as well as observations, and supported by documentation studies. Data analysis was conducted with the help of the Atlas.ti 9 software to map the relationships between managerial variables. The results show that the HR management strategy is carried out through an integrated cycle, including: 1) Linearity-based planning and real needs analysis; 2) Competency development through applied training and inter-disciplinary collaboration; 3) Reflection-based performance evaluation for policy making; and 4) Internalization of Islamic organizational culture as a reinforcement of moral integrity. Although the reward system has been implemented, the aspect of transparency remains a note for future development. In conclusion, the synergy between administrative support, sustainable capacity development, and spiritual values is key to creating a solid ecosystem of teacher professionalism in elementary schools.